Evaluation of EOA and its changes in one year follow up in patients with stentless biological 3F valve (ATS-Medtronic, Minnapolis) made of equine pericardium - Bartuś, Krzysztof; Sadowski, Jerzy; Kapelak, Bogusław; Myć, Jacek; Bartuś, Stanisław; Oleś, Krzysztof; Filip, Grzegorz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Background : One of the most important factors affecting outcomes is effective orifice area (EOA). Aim : Evaluation of EOA and its changes in one year follow up in patients with stentless biological 3F valve (ATS- Medtronic, Minneapolis). Material and methods : 45 patients aged from 23-78 years, received biological stentless 3F (ATS-Medtronic) valves. Patients were followed up for one year. Results: In the early postoperative period (30 days) the effective orifice area (EOA) was 2.6 cm 2 (± SD = 0.8). Effective orifice area index (EOAI) = 1.3 cm 2 (± SD = 0.3). 3-6 months post op EOA = 2.4 cm 2 (± SD = 0.8). EOAI = 1.24 cm 2 (± SD = 0.4). At one year EOA = 2.51 cm 2 (± SD = 0.6). EOAI = 1.32 cm 2 (± SD = 0.3). Differences in the effective orifice area for each valve size did not show statistically significant changes at one year postoperative control. Conclusions : 1. Based on the results valve has relatively big EOA. 2. Results suggest that EOA may be bigger than in other publications. 3. There were no significant changes in EOA in one year follow up.